The Influence of Brand Image, Advertising, and Discount Prices on Purchase Intention at CV Putra Jaya - Wulandari, Desi; Wisnu Setya Bhirawa , Sigit (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This study investigates the influence of brand image, advertising, and discount prices on purchase intention at CV Putra Jaya. The research aims to determine the extent to which these factors drive consumer behavior and contribute to marketing effectiveness. Design/Methode/Approach : The study adopts a quantitative research approach, utilizing survey data collected from 40 respondents who are customers or potential customers of CV Putra Jaya. This research was designed with a causal research design with a quantitative approach, namely test. Research Finding : The results indicate that brand image and advertising have a significant positive effect on purchase intention, while discount prices demonstrate a moderate effect. Among these factors, brand image emerged as the strongest predictor of purchase intention, highlighting its critical role in shaping consumer decisions. Theoretical contribution/Originality : This research contributes to the literature by integrating brand image, advertising, and discount pricing as simultaneous predictors of purchase intention, providing a holistic perspective on consumer behavior in the retail sector. Practitionel/Policy implication : The findings suggest that businesses like CV Putra Jaya should prioritize enhancing brand image and creating impactful advertising campaigns while strategically using discounts to boost sales without undermining perceived value. Research limitation : The study focuses on a single retail company and its customers, which may limit the generalizability of the findings. Future research could explore other industries or comparative analyses across regions.